Clear Lens Extraction with Foldable Intraocular Lens Implantation in a Case of Isolated Microspherophakia - Shrestha, Chunu; Pandey, Manish (Medical Journal of Shree Birendra Hospital, 2016)
Microspherophakia is an uncommon bilateral eye condition in which there is abnormal laxity of the lens zonules, leading to development of a spherical lens. Microspherophakia without systemic features is a rare presentation. The management of such a case is quite challenging. We report a case of isolated microspherephakia which was managed successfully with clear lens extraction with implantation of a foldable intraocular lens.